The Podocyte in Diabetic Kidney Disease - Erin Stitt-Cavanagh; Laura MacLoed; Chris R.J. Kennedy (The Scientific World Journal)
Approaching epidemic levels, diabetic kidney disease (DKD) is now the leading cause of end-stage renal disease (ESRD). Microalbuminuria is an early clinical marker of DKD that results from damage to the glomerular filtration barrier at the level of the highly differentiated glomerular podocyte cells. Injury to these epithelial cells, podocytopathies, includes cellular hypertrophy, foot process effacement, detachment from the glomerular basement membrane, and apoptosis. Here we review the role of a number of recently identified factors that contribute to podocytopathies in DKD. These factors include members of the renin-angiotensin system (RAS), including angiotensin-converting enzyme (ACE) types 1 and 2, prorenin and its receptor, reactive oxygen species (ROS), prostanoids, peroxisome proliferator-activated receptors (PPAR), advanced glycation end-products (AGEs) and their receptors (RAGE), adiponectin, and microRNAs. As the number of therapeutic options that slow, but do not halt, the progression of DKD to ESRD remains limited, a more comprehensive understanding of the signaling events that contribute to this increasingly prevalent disease may identify novel avenues for treatment and prevention.